Професійна ідентичність майбутніх поліцейських на її когнітивному рівні - Макарова, О. П.; Makarova, O. P.; ORCID: http://orcid.org/0000-0002-5480-5942 (Вісник Національного університету оборони України. - 2019. - №1(51). - С. 74-83, 2019)
Розглянуто розвиток професійної ідентичності поліцейських під час навчання у вищому навчальному закладі зі специфічними умовами навчання. Визначено рівні професійної ідентичності. Висвітлено результати емпіричного дослідження професійної ідентичності на когнітивному рівні.

Professional identity refers to the concepts, which emphasize the conceptual representation of a personality about his place in a professional group. That is, the connection of personal characteristics that provide orientation in the world of professions, the professional identity is highlighted as an integrative concept that allows more fully realize the personal potential within professional activities. Professional identity is formed in the process of personal identity and is an indicator of professionalism. The quality of professional training of police officers is of particular importance with the growth of the crime situation in the country. In today’s conditions, we need a professional who is capable to effectively combat crime, to confidently and reliably protect citizens from criminal encroachments. As a result, graduates of higher education institutions with specific learning conditions must have the requirements for both possess certain knowledge and skills, to observe the legality in professional and everyday life and be able to make decisions independently for performing official and operative tasks. The urgency of the development of professional identity in the system of departmental education of internal affairs agencies is aggravated by the fact that the client is a specifically defined organization – the Ministry of Internal Affairs, which makes explicit demands to a modern specialist – a law enforcement officer. Having analyzed the research in the direction of developing professional identity, it became clear that nowadays it is not enough to have research works that would be aimed at studying the development of the professional identity of future police officers, especially while being trained at a higher educational institution with specific learning conditions. In this regard, the problem of studying the development of the professional identity of future police officers becomes relevant. The objective is theoretical and empirical study of the peculiarities for forming the components of the professional identity of future police officers at different levels, namely, at the cognitive level.

Рассмотрено развитие профессиональной идентичности полицейских во время обучения в высшем учебном заведении со специфическими условиями обучения. Определены уровни профессиональной идентичности. Отражены результаты эмпирического исследования профессиональной идентичности на когнитивном уровне.
Professional identity of future police officers at their cognitive level
Профессиональная идентичность будущих полицейских на ее когнитивном уровне
Макарова, О. Професійна ідентичність майбутніх поліцейських на її когнітивному рівні / Макарова О. // Вісник Національного університету оборони України. - 2019. - №1(51). - С. 74-83. - DOI: 10. 33099/2617-6858 – 2019 – 51– 1 – 74-83.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Юридична психологія. Legal psychology. Юридическая психология; майбутні поліцейські; future police officers; будущие полицейские; професійна ідентичність; professional identity; профессиональная идентичность; когнітивний рівень; cognitive level; когнитивный уровень; фахова підготовка; professional preparation; профессиональная подготовка; професійне становлення особистості; professional formation of the personality; навчальні заклади зі специфічними умовами навчання